Effects of Inquiry Instruction with Gamification on Concepts and Motivation towards Learning Biology of Upper Secondary School Students - Pathomjaroenponkul, Nattawut; Kaewdee, Sakolrat (An Online Journal of Education, 2026)
This research employed a quasi-experimental design and aimed to: 1) compare the upper secondary students’ biology concept of photosynthesis before and after learning with the inquiry-based learning with gamification, 2) investigate the students’ biology concept of photosynthesis before and after instruction, 3) compare students’ motivation to learn biology before and after instruction, and 4) analyze student’s motivation to learn biology during instruction. The target population consisted of 36 eleventh-grade students from a demonstration school under the Ministry of Higher Education, Science, Research and Innovation in Nakhon Pathom. The selection method was cluster sampling, with one classroom randomly selected. The experiment instruments included four biology lesson plans on photosynthesis. Data collection instruments comprised a biology concept test, a biology learning motivation test, and a behavioral observation form indicating learning motivation. The research findings indicated that 1) students’ concept scores after instruction were significantly higher than before instruction, at the .05 level of statistical significance 2) students’ conceptual understanding after instruction were higher than before instruction 3) students’ motivation level after instruction were significantly higher than before instruction, at the .05 level of statistical significance, and 4) students had a high level of motivation during the inquiry-based learning with gamification.